Between mourning and melancholia: Religion and politics in modern India. Issue 3 (1st September 2016) - Ahmad, Irfan
Abstract: In reviewing this autobiographical book by Saeed Naqvi, an internationally known Indian journalist, this essay first discusses the relationship amongst journalism, autobiography and anthropology, the discipline this reviewer broadly works in. Arguing for a crossover amongst them, it documents the evolving relationships Naqvi describes between religion and politics in modern India, including the moment of India's Partition in 1947. It discusses such figures as Azad, Gandhi, Nehru, Patel, Rao, Vajpayee and issues such as ethnic/communal violence, the role of the state in genocide, demolition of Babri Masjid, the US-led "Global War On Terror (GWOT)" and more. This essay notes the salience of Naqvi's thesis that the much-valorized Indian secularism was and is at best a mask for majoritarian religious impulse. However, it critiques Naqvi's solution as a return to India's founding fathers and the imagined era of so-called composite culture. Central to this critique is the point that Naqvi's own personal and professional account of colonial and postcolonial India defies his proposed solution. This paradox appears precisely because Naqvi, this essay suggests, mourns a past which he is unable to identify, let alone enunciate. His account thus approximates, following Freud, melancholia more than mourning.